2003
DOI: 10.1093/tropej/49.4.216
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Malaria in Children: Serum and Cerebrospinal Fluid TNF‐α and TGF‐β Levels and Their Relationship to Clinical Outcome

Abstract: This was a prospective study conducted at the Moi Teaching and Referral Hospital, Eldoret, Kenya. Twenty-three children admitted to the hospital with cerebral (CM) and 10 children with non-cerebral malaria (NCM) were studied. The aim of the study was to establish and compare levels of tumour necrosis factor (TNF-alpha) and transforming growth factor (TGF-beta1) in these children. Serum and cerebrospinal fluid (CSF) cytokine levels were assayed using ELISA kits. In serum, TGF-beta1 and TNF-alpha decreased over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…The finding of lower TGF-β1 concentrations with increasing disease severity in the present study is consistent with most [13, 26, 27] though not all [30, 43] prior studies. TGF-β1 in vitro inhibits development of effector T-cells and macrophage activation and has less effect once those cells have been activated [44, 45].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The finding of lower TGF-β1 concentrations with increasing disease severity in the present study is consistent with most [13, 26, 27] though not all [30, 43] prior studies. TGF-β1 in vitro inhibits development of effector T-cells and macrophage activation and has less effect once those cells have been activated [44, 45].…”
Section: Discussionsupporting
confidence: 93%
“…Results were interpolated from standard curves generated with SoftMax software (Molecular Devices). Concentrations of interleukin-1beta (IL–1β) [3], interleukin 6 (IL-6) [8], interferon gamma (IFN–γ) [9], tumour necrosis factor alpha (TNF- α) [30], macrophage inflammatory protein alpha (MIP–1α) [31], and macrophage inhibitory protein beta (MIP-1β) [32], which have been associated with increased risk of severe disease and/or death in malaria, and of RANTES, which have been associated with a decreased risk of severe disease and death in malaria [11], were determined by a commercially available cytometric bead assay (CBA)(R&D Systems) using the Luminex system and have been previously published [11]. …”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…Point (3) for the cytokine hypothesis is questionable with some studies showing a clear increase in TNF in CM, which is even higher in fatal cases in African children (Grau et al, 1989; Kwiatkowski et al, 1990; Sahu et al, 2013), but more recent studies have shown no correlation between TNF concentration and CM (Esamai et al, 2003; Armah et al, 2007; Thuma et al, 2011). Other cytokines have been implicated too (Hunt and Grau, 2003; Boeuf et al, 2012; Ioannidis et al, 2014), but the results of these studies are hard to interpret as it depends on which control group it is compared to; NCM, severe malarial anemia, other encephalitis, other febrile illnesses or even healthy individuals.…”
Section: Pathogenesis Of CMmentioning
confidence: 99%
“…In a study conducted in the highlands of western Kenya, serum levels of TNF-α and TGF-β correlated negatively inCM and non-CM patients [139]. The serum TGF-β1 levels tended to be higher for children with shorter duration and lower for those with longer duration of illness before admission in both CM and non-CM [139].…”
Section: Role Of Il-10 Tgf-β Other Cytokines and Regulatory T Cellsmentioning
confidence: 99%
“…The serum TGF-β1 levels tended to be higher for children with shorter duration and lower for those with longer duration of illness before admission in both CM and non-CM [139]. There were lower levels of TGF-β in children with deeper coma compared to those with lighter degrees of coma [139]. …”
Section: Role Of Il-10 Tgf-β Other Cytokines and Regulatory T Cellsmentioning
confidence: 99%